Clostridioides difficile infection is associated with differences in transcriptionally active microbial communities - Chen See, Jeremy R.; Leister, Jillian; Wright, Justin R.; Kruse, Peter I.; Khedekar, Mohini V.; Besch, Catharine E.; Kumamoto, Carol A.; Madden, Gregory R.; Stewart, David B.; Lamendella, Regina (Frontiers in Microbiology, 2024)
Clostridioides difficile infection (CDI) is responsible for around 300,000 hospitalizations yearly in the United States, with the associated monetary cost being billions of dollars. Gut microbiome dysbiosis is known to be important to CDI. To the best of our knowledge, metatranscriptomics (MT) has only been used to characterize gut microbiome composition and function in one prior study involving CDI patients. Therefore, we utilized MT to investigate differences in active community diversity and composition between CDI+ (n=20) and CDI-(n=19) samples with respect to microbial taxa and expressed genes. No significant (Kruskal-Wallis, p>0.05) differences were detected for richness or evenness based on CDI status. However, clustering based on CDI status was significant for both active microbial taxa and expressed genes datasets (PERMANOVA, p≤0.05). Furthermore, differential feature analysis revealed greater expression of the opportunistic pathogens Enterocloster bolteae and Ruminococcus gnavus in CDI+ compared to CDI-samples. When only fungal sequences were considered, the family Saccharomycetaceae expressed more genes in CDI-, while 31 other fungal taxa were identified as significantly (Kruskal-Wallis p≤0.05, log(LDA)≥2) associated with CDI+. We also detected a variety of genes and pathways that differed significantly (Kruskal-Wallis p≤0.05, log(LDA)≥2) based on CDI status. Notably, differential genes associated with biofilm formation were expressed by C. difficile. This provides evidence of another possible contributor to C. difficile's resistance to antibiotics and frequent recurrence in vivo. Furthermore, the greater number of CDI+ associated fungal taxa constitute additional evidence that the mycobiome is important to CDI pathogenesis. Future work will focus on establishing if C. difficile is actively producing biofilms during infection and if any specific fungal taxa are particularly influential in CDI.